Effects of microbial biocontrol agents on tea plantation microecology and tea plant metabolism: a review - Xie, Yixin; Cao, Chunxia; Huang, Daye; Gong, Yan; Wang, Beibei (Frontiers in Plant Science, 2025)
The quality of fresh tea leaves is crucial to the final product, and maintaining microbial stability in tea plantations is essential for optimal plant growth. Unique microbial communities play a critical role in shaping tea flavor and enhancing plant resilience against biotic stressors. Tea production is frequently challenged by pests and diseases, which can compromise both yield and quality. While biotic stress generally has detrimental effects on plants, it also activates defense metabolic pathways, leading to shifts in microbial communities. Microbial biocontrol agents (MBCAs), including entomopathogenic and antagonistic microorganisms, present a promising alternative to synthetic pesticides for mitigating these stresses. In addition to controlling pests and diseases, MBCAs can influence the composition of tea plant microbial communities, potentially enhancing plant health and resilience. However, despite significant advances in laboratory research, the field-level impacts of MBCAs on tea plant microecology remain insufficiently explored. This review provides insights into the interactions among tea plants, insects, and microorganisms, offering strategies to improve pest and disease management in tea plantations.